2018
DOI: 10.1111/jspn.12219
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a nail‐biting prevention program among primary school students

Abstract: The program significantly reduced the nail-biting rate among primary school students. The nurse that implement this program will be able to do a comprehensive evaluation of students' nail-biting habits, perform solution-focused interventions, and prevent advanced complications that might develop in connection to nail-biting. Thus, the effectiveness of nursing implementations will improve in the prevention of nail-biting habit, early diagnosis, and changing students' habits. "Do Not Bite Your Nails, Cut Your Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…The differences in this domain could be attributed to students' focus on the breastfeeding training that they would give to women who had recently given birth, whereas the educators could interact with the women with a more holistic point of view. Although the study by Gür et al [11] identified most of the problems to be in the physiological domain, the teeth were reported to be the fourth most important problem. Aylaz et al [1] found that 36.4% of the individuals had inadequate oral and dental care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in this domain could be attributed to students' focus on the breastfeeding training that they would give to women who had recently given birth, whereas the educators could interact with the women with a more holistic point of view. Although the study by Gür et al [11] identified most of the problems to be in the physiological domain, the teeth were reported to be the fourth most important problem. Aylaz et al [1] found that 36.4% of the individuals had inadequate oral and dental care.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature showed studies which used the Omaha System in occupational health nursing, school health nursing, nursing homes and some clinical fields [6,[9][10][11][12][13][14]. These studies focused specifically on the use of the Omaha System.…”
mentioning
confidence: 99%
“…Furthermore, the study showed that knowledge about difference between personal and general hygiene requirements was witnessed also knowledge of pupils about the harm of nails biting on health was showed increase after health education intervention. A study conducts to assess the effectiveness of nail-biting prevention program in turkey found that children's frequency of biting their nail varies, 57.7% children bite their nail occasionally, and 11.7% children bite their nail all the time, however, 30.8% children replied that they have habit of biting nail seldom (Gür et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A nail-biting program under the title of "Do Not bite nail, but cut your nail" conducted in primary school in turkey found that children can also be adopted nail biting habit if someone around them has nail biting habits. 50.8% of the children reported that their mother has habit of nail biting, 28.8% asked about their father, 9.4% said brother/sister were nail biter, however only 1.7% children don't have anyone around them who have habit of nail biting (Gür et al, 2018). Another study explore that many parents worried about the nail-biting habit of their children, they done multiple options to stop nail biting such as punish their children even put them under stress, but unfortunately these practices are not affective for long time (Ergun et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…[1] , [2] , [3] , [4] , [5] , [9] , [11] , [13] , [17] , [19] , [27] , [32] , [33] , [34] , [36] , [43] , [44] , [47] , [49] , [53] , [54] , [56] .…”
Section: Uncited Referencesunclassified